Pravna narava obveznosti po 68.a členu Zakona o davčnem postopku - Podlipnik, Jernej (Podjetje in delo, 2016)
The article deals with the legal nature of the monetary obligation according to Article 68.a of the Slovenian Tax Procedure Act. Although it is named special tax on individuals' unreported income the author argues that it cannot be, at least not as a whole, classified as tax, but rather as a special administrative sanction, because individuals are burdened more than they would be if regular income taxes were levied on them. Despite administrative sanctions are one of means to tackle tax frauds, the constitutionality of the legislation in question is doubtful from the substantive and procedural point of view.
Keywords: davčne utaje; davčni nadzor; davčni postopek; davki; sankcije